2022
DOI: 10.26434/chemrxiv-2022-gznb4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significant Impact of Deprotonated Status on the Photoisomerization Dynamics of Bacteriophytochrome Chromophore

Abstract: We report that the photoinduced dynamics of the phytochrome chromophore is strongly dependent on the protonation/deprotonation states of the pyrrole ring. The on-the-fly surface hopping dynamics simulations were performed to study the photoisomerization of different protonation/deprotonation phytochrome chromophore models. The simulation results indicate that the deprotonations at the pyrrole rings significantly modify the photoinduced nonadiabatic dynamics, leading to distinctive population decay dynamics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In addition, the hydrogen-bond network patterns greatly affect the photoisomerization channels of central chromophores, when a different deprotonation status exists in these pyrrole rings. 35,36 These works demonstrated that the photoisomerization of phytochrome chromophores may be adjusted by the distinctive confinement of chromophores in the vacuum and in the surrounding environment. In a vacuum, the chromophore is a ''free'' molecule and the rotation of any carbon-carbon bond is not affected by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hydrogen-bond network patterns greatly affect the photoisomerization channels of central chromophores, when a different deprotonation status exists in these pyrrole rings. 35,36 These works demonstrated that the photoisomerization of phytochrome chromophores may be adjusted by the distinctive confinement of chromophores in the vacuum and in the surrounding environment. In a vacuum, the chromophore is a ''free'' molecule and the rotation of any carbon-carbon bond is not affected by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…18 Such an active space size is computationally intractable since the maximum size currently achievable is 18 electrons in 18 orbitals. 19 Therefore, in previous studies a compromise was chosen to either employ approximate electronic structure methods, such as a semi-empirical method, [20][21][22] or to truncate the chromophore. [23][24][25][26][27][28] In the latter approach, typically, the propionic acid groups 23,29 are replaced by hydrogen atoms because they are not part of the conjugated psystem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hydrogen-bond network patterns greatly affect the photoisomerization channels of central chromophores, when different deprotonation status exist in these pyrrole rings. 33,34 These works demonstrated that the photoisomerization of phytochrome chromophores may be adjusted by the distinctive confinement of chromophores in the vacuum and in the surrounding environment. In a vacuum, the chromophore is a "free" molecule and the rotation of any carbon-carbon bond is not affected by external factors.…”
Section: Introductionmentioning
confidence: 99%